When Moon Blooms - Salazar, Aida; Benavides, Caribay M., 1989- (New York : Rise x Penguin Workshop, 2024)
As a child admires the moon, their mother imparts Mexican Indigenous wisdom of the moon's phases as they relate to our bodies and lives.
new kids book 2024 spring.
Ages 2-4.
Keywords: Planets -- Phases; Bedtime & Dreams; Science & Nature; Parent and child -- Fiction; Mexican Americans -- Fiction; Moon -- Phases -- Fiction; Picture books